Keadilan Ekologi Berbasis Gender: Kritik atas Antroposentrisme Hukum Lingkungan di Indonesia - Safitri, Sena Putri (Primagraha Law Review, 2025)
The ecological crisis in Indonesia shows that environmental damage does not only stem from exploitative behavior towards nature, but also from a legal paradigm that places humans at the center of interest. Regulations on Environmental Protection and Management are still rooted in an anthropocentric view that sees nature as an economic object. This paradigm has given rise to ecological inequality and gender inequality, as women are often the most affected group but are least accommodated in environmental policies. The purpose of this study is to critique the anthropocentric bias in Indonesian environmental law by offering an alternative paradigm based on ecological justice and gender equality. The research method used is normative legal research with a conceptual, legislative, and legal philosophy approach. The results show that the integration of ecocentric and ecological feminist perspectives can reconstruct environmental law towards a more inclusive, fair, and sustainable system.